Luminal bacteria coated with IgA and IgG during intestinal inflammation as a new and abundant stimulus for colonic macrophages. Issue 1 (25th June 2022) - Maccio‐Maretto, Lisa; Piqueras, Virginia; Barrios, Bibiana E.; Romagnoli, Pablo A.; Denning, Timothy L.; Correa, Silvia G.
Abstract: In the gut, secretory immunoglobulin A is the predominant humoral response against commensals, although healthy hosts also produce microbiota‐specific IgG antibodies. During intestinal inflammation, the content of IgG in the lumen increases along with the proportion of commensal bacteria coated with this antibody, suggesting signalling through the IgG‐CD64 axis in the pathogenesis of inflammatory bowel diseases. In this work, we evaluated day by day the frequency of faecal bacteria coated with IgA and IgG during the development of DSS colitis. We studied the phenotype and phagocytic activity of F4/80 + CD64 + colonic macrophages, as well as the production of cytokines and nitric oxide by lamina propria or bone marrow‐derived macrophages after stimulation with IgA +, IgG + and IgA + IgG + bacteria. We found that the percentage of faecal IgA + IgG + double‐coated bacteria increased rapidly during DSS colitis. Also, analysis of the luminal content of mice with colitis showed a markedly superior ability to coat fresh bacteria. IgA + IgG + bacteria were the most potent stimulus for phagocytic activity involving CD64 and Dectin‐1 receptors. IgA + IgG + bacteria observed during the development of DSS colitis could represent a new marker to monitor permeability and inflammatory progression. The interaction of IgA + IgG + bacteria with CD64 + F4/80 + macrophages could be part of the complex cascade of events in colitis. Interestingly, after stimulation, CD64 + colonic macrophages showed features similar to those of restorative macrophages that are relevant for tissue repair and healing. Abstract : In homeostasis, the intestinal lamina propria presents F4/80+ cells expressing CD64. These cells are distributed homogeneously and secrete regulatory cytokines such as IL10. The presence of double‐positive (IgA+IgG+) bacteria is scarce; the mucus barrier and the intact epithelial layer allow for immune exclusion (left). In inflammatory conditions, levels of IgG in the lumen are promptly increased; loss of epithelial integrity and mucus discontinuity enable the mucosa invasion by double‐positive bacteria. F4/80+CD64+ macrophages consolidate around tissue injury foci, displaying a restorative phenotype with higher phagocytic activity and IL6/TNFα release (right).